Optimasi Komposisi Makanan Penderita Diabetes dengan Hybrid Genetic Algorithm dan Modified Simulated Annealing - Achmad Suryadi Nasution; Ilham Saputra; Anisa Nur Rosidha; Lutfi Mardianto (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
Diabetes mellitus is one of the deadliest diseases. Factors that can cause diabetes mellitus are irregular eating patterns and unhealthy lifestyles. Patients with diabetes mellitus must have a healthy diet by identifying the optimal food composition so as not to trigger complications with various other deadly diseases. Identification of food composition was carried out using a hybrid adaptive genetic algorithm and modified simulated annealing. Based on the patient testing results, the average accuracy for carbohydrates, protein, fat, sodium, fiber, and calories was 99.90%, 99.72%, 99.33%, 99.99%, 99.29%, and 99.86%, respectively.